Survivin expression as an independent predictor of overall survival in malignant peritoneal mesothelioma - Zhang, Guozun (Oncol Lett, 2020)
Malignant peritoneal mesothelioma (MPeM) is an incurable cancer strongly associated with asbestos exposure and characterised by poor prognosis. The aim of the present study was to elucidate the prognostic and predictive value of CD146 and survivin expression in MPeM. Diagnostic biopsies from 60 patients with MPeM were collected and analysed for CD146, survivin and Ki-67 expression using immunohistochemistry. Complete clinical and follow-up information was obtained from patients' records. CD146 was expressed in 31/60 MPeM specimens and survivin in 34/60 specimens, with both expression levels being significantly associated with the Ki-67 labelling index (Ki-67LI). Kaplan-Meier and univariate Cox regression analyses revealed that a lower peritoneal cancer index (PCI), tumour-directed treatment, stage I, lower Ki-67LI and lower CD146 and survivin expression had a statistically positive effect on overall survival (OS). Cox regression analysis revealed that PCI [hazard ratio (HR)=1.99; 95% CI, 1.04–3.83; P=0.038], survivin (HR=1.47; 95% CI, 1.03–2.10; P=0.034) and treatment protocol including intraperitoneal chemotherapy (HR=0.28; 95% CI, 0.14–0.57; P=0.013) and systemic chemotherapy (HR=0.13; 95% CI, 0.04–0.42; P=0.013) retained independent prognostic significance for OS. All of these were included in the nomogram. Calibration curves showed good agreement between nomogram-predicted and observed survival. The C-index of the nomogram for predicting OS was 0.77. A lower PCI, intraperitoneal chemotherapy, systemic chemotherapy and a lower level of survivin were powerful prognostic markers in patients with MPeM. The proposed nomogram provides individual survival prediction for patients with MPeM.